1959
DOI: 10.1021/ac60156a053
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Arsenic in Petroleum Stocks and Catalysts by Evolution as Arsine

Abstract: However, heating the bath formulation to 100" C. made a difference. No color developed a t 0.4 but a blue color appeared at the point of origin on the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1962
1962
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Typical arsenic concentration in naphtha ranges from v1 to 40 mg L 21 . 2,[6][7][8][9][10][11][12][13] In 1959, Powers et al suggested arsenic would be present in naphtha as alkyl arsines. 2 Studies conducted by Puri and Irgolic in 1989 revealed that trimethylated and monomethylated arsenic are, in fact, the predominant arsenic species in petroleum products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical arsenic concentration in naphtha ranges from v1 to 40 mg L 21 . 2,[6][7][8][9][10][11][12][13] In 1959, Powers et al suggested arsenic would be present in naphtha as alkyl arsines. 2 Studies conducted by Puri and Irgolic in 1989 revealed that trimethylated and monomethylated arsenic are, in fact, the predominant arsenic species in petroleum products.…”
Section: Introductionmentioning
confidence: 99%
“…7 In the following years, other authors proposed different methodologies based on spectrophotometric determinations of arsenic as molybdenum blue or silver diethyldithiocarbamate complexes. 2,6,8,9 Those methods all have in common the laborious and time-consuming sample pretreatment step for matrix separation or analyte preconcentration, such as wet acid digestion, combustion, liquid-liquid extraction, distillation and arsine generation.…”
Section: Introductionmentioning
confidence: 99%
“…Soil As was determined by extraction with concentrated HC1, ASH3 was generated on the extract by the Gutzeit proce dure, and then estimated by the silver diethyldithiocarbamate procedure (3).…”
Section: Methodsmentioning
confidence: 99%
“…Leaders in the apple industry recognize that high quality is of utmost importance to satisfy consumers and stimulate repeat sales (3). They urged the expansion of research to develop objective measurements of quality factors for use in grading and segregating fruit for storage or marketing.…”
Section: A D D Itio N a L Index W Ords M Alus Dom Estica Firm Ness Cr...mentioning
confidence: 99%